Az Állami Díjas szövőnőktől a tenyérjóslásig: A Nõk Lapja 1989-tõl 1999-ig - Tóth, Olga (Szociológiai Szemle, 2024)
The paper presents the changes of the fifty year-old Hungarian women's magazine, Nők Lapja as they have occurred during the past decade. Not only the inner structure of the magazine but also the role models, presented by the reports, were analysed. In the late eighties and early nineties Nők Lapja was the only popular women's magazine. It had a culture-oriented structure. The ratio of advertisements was low and articles of report-type made up one-third of the pages. By the end of the nineties the relative importance of reports decreased to one-fifth, while advertisements took up one-fourth of the pages. Esoteric materials, horoscopes and palmistry became very important columns of the magazine. The role models, presented by Nők Lapja, have also changed. In 1989 70.5% of women, presented in the reports, were common people. In 1999 the ratio of such common people dropped to 42%. At the same time the ratio of famous women (models, actresses, pop stars) increased. Work and politics were pushed into the background by the end of the period, while traditional family life and the tricks of beauty and fitness acquired greater importance. The gender roles presented have been very much of a stereotype and feminism is given a negative connotation in Nők Lapja.